Soziale Inklusion - Reinelt, André (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
In recent years, the law has observed an increasing number of access conflicts in purely private law contexts. Based on the BVerfG's stadium ban decision, this study shows that the institute of the contract plays a central role in this context. By combining a multilateral perspective and insights from differentiation theory, it is argued that the contract fulfills an inclusion function in modern society. In particular, the general principle of equality is highly responsive to mediate social inclusion conflicts in law. The thesis sees in the participation dimension the convincing connecting factor to justify its effect in private law. The work was awarded the 'Preis der Stadt Bayreuth‘ and the ‚Carl-Gareis-Preis‘ of the University of Bayreuth.